Long-Acting Thioredoxin Ameliorates Doxorubicin-Induced Cardiomyopathy via Its Anti-Oxidative and Anti-Inflammatory Action - Ryota Murata; Hiroshi Watanabe; Hiroto Nosaki; Kento Nishida; Hitoshi Maeda; Motohiro Nishida; Toru Maruyama (Pharmaceutics, 2022)
Although the number of patients with heart failure is increasing, a sufficient treatment agent has not been established. Oxidative stress and inflammation play important roles in the development of myocardial remodeling. When thioredoxin (Trx), an endogenous anti-oxidative and inflammatory modulator with a molecular weight of 12 kDa, is exogenously administered, it disappears rapidly from the blood circulation. In this study, we prepared a long-acting Trx, by fusing human Trx (HSA-Trx) with human serum albumin (HSA) and evaluated its efficacy in treating drug-induced heart failure. Drug-induced cardiomyopathy was created by intraperitoneally administering doxorubicin (Dox) to mice three times per week. A decrease in heart weight, increased myocardial fibrosis and markers for myocardial damage that were observed in the Dox group were suppressed by HSA-Trx administration. HSA-Trx also suppressed the expression of atrogin-1 and myostatin, myocardial atrophy factors in addition to suppressing oxidative stress and inflammation. In the Dox group, a decreased expression of endogenous Trx in cardiac tissue and an increased expression of macrophage migration inhibitory factor were observed, but these changes were restored to normal levels by HSA-Trx administration. These findings suggest that HSA-Trx improves the pathological condition associated with Dox-induced cardiomyopathy by its anti-oxidative/anti-inflammatory and myocardial atrophy inhibitory action.